Observing the report "H-index of spanish scientific journals according to Google Scholar Metrics": the case of the art journals: Observing the report "H-index of spanish scientific journals according to Google Scholar Metrics": the case of the art journals - CRESPO-FAJARDO, José Luis; PILLACELA-CHIN, Luisa (Utopía y Praxis Latinoamericana, 2021)
This article reflects on the annual report prepared by the research group EC3 (Evaluation of Science and Scientific Communication), of the University of Granada, entitled " H-index of Spanish scientific journals according to Google Scholar Metrics", focusing on the section of art journals. It assesses their accuracy, explaining the convenience of categorizing journals by discipline and the need to remove non-scientific journals. It warns about the consequences that the lack of precision of the report could generate in the community of researchers and in the evaluation agencies.